Correlation between microalbuminuria & lipid profile in acute ischemic stroke - Chowdhury, J; Sultana, N; Ahmed, S; Hossain, MZ; Akhter, F; Sultana, N; Begum, S (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13239 J. Dhaka Med. Coll. 2012; 21(1): 55-59